If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying r + -6h = 5n + yr Reorder the terms: -6h + r = 5n + yr Solving -6h + r = 5n + ry Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '-1r' to each side of the equation. -6h + r + -1r = 5n + -1r + ry Combine like terms: r + -1r = 0 -6h + 0 = 5n + -1r + ry -6h = 5n + -1r + ry Divide each side by '-6'. h = -0.8333333333n + 0.1666666667r + -0.1666666667ry Simplifying h = -0.8333333333n + 0.1666666667r + -0.1666666667ry
| 2+4+(3-4)=3+12 | | 10g+180=3g+54 | | yr+5n=r-6h | | 6(x-1)-x=22-2x | | 40z^2+12-12=0 | | 6x-9=24x+3 | | V-7v=12 | | 15=4(x-3)-(x-9) | | 9=-5n+1+3 | | 4x^2-4x+7x-7=2x-1 | | -4+9(6y+3)=(4y-5)-4 | | 4(x-5)+12=8 | | 32x+4y=0 | | f(x)=50cos(7*(x^6)) | | (x+1)(3x+1)=96x^2 | | 16+5(6c-3)= | | x(x+1)=x(x+1)+5 | | 5ab+8ab= | | 2[7-(-4x-5)]=32x+54 | | 5x+4x+4=x+6x+16 | | T=(7+RS) | | T=(7+RS)forS | | -8+5u=-33 | | 8x+a-12=4x-13-5x | | 5t(9t+4)=0 | | s=4k+4 | | 8t+6=6+7t | | (4z+5)(3-z)=0 | | 13x+24x-31x=144 | | 7y+2=6y-2 | | 3x^2-12x-180=0 | | 3y+8=2y-6 |